2011
DOI: 10.1037/a0022647
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the temporal stability of self-report and interview assessed personality disorder.

Abstract: Findings from several large-scale, longitudinal studies over the last decade have challenged the long held assumption that personality disorders (PDs) are stable and enduring. However, the findings, including those from the Collaborative Longitudinal Personality Disorders Study (CLPS; Gunderson et al., 2000), rely primarily upon results from semistructured interviews. As a result, less is known about the stability of PD scores from self-report questionnaires, which differ from interviews in important ways (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 65 publications
8
55
0
Order By: Relevance
“…However comparing confidence intervals is the only method available for kappas derived from dependent samples (McKenzie et al, 1996; Samuel et al, 2011). It is noteworthy that the confidence intervals for four diagnoses—MDD, OCD, Social Phobia, and Dysthymia—do not overlap, clearly indicating a significant difference across method.…”
Section: Resultsmentioning
confidence: 99%
“…However comparing confidence intervals is the only method available for kappas derived from dependent samples (McKenzie et al, 1996; Samuel et al, 2011). It is noteworthy that the confidence intervals for four diagnoses—MDD, OCD, Social Phobia, and Dysthymia—do not overlap, clearly indicating a significant difference across method.…”
Section: Resultsmentioning
confidence: 99%
“…This general finding was cited as a major reason for developing a revised system for characterizing and diagnosing PDs published in Section III (Emerging Models and Measures) of the DSM-5 (Skodol et al, 2011). Although past research suggests that dimensional assessments of PD traits are more stable than disorders or symptom counts (Hopwood et al, 2013; Morey et al, 2007; Samuel et al, 2011), the longitudinal (i.e., > 1 year) stabilities of the DSM-5 traits remain unknown. The current study was conducted to determine the mean-level, rank-order, and individual stability of the DSM-5 PD traits, as well as the longitudinal associations among traits and psychosocial functioning.…”
mentioning
confidence: 99%
“… 3 The self-reported criteria in Samuel et al (2011) were drawn from the Schedule for Nonadaptive and Adaptive Personality (Clark, 1993), whereas Lenzenweger (1999) used the Millon Clinical Multiaxial Inventory – II (Millon, 1987). …”
mentioning
confidence: 99%
“…Markon, Chmielewski, and Miller (2011) found that continuous variables are substantially more reliable and valid than categorical variables. It follows that estimates of the differential and absolute stability of personality disorder tend to be higher when they are treated as continuous symptom counts rather than diagnostic categories (Samuel et al, 2011).…”
Section: Assessmentmentioning
confidence: 99%
“…Research comparing these methods generally finds that questionnaires produce relatively higher stability estimates than diagnostic interviews. For instance, in the CLPS study, Samuel et al (2011) found that the 2-year differential stability was r = .69 for a questionnaire measure and r = .60 for an interview, whereas the absolute change was d = .21 for the questionnaire and d = .30 for the interview.…”
Section: Assessmentmentioning
confidence: 99%